2000
DOI: 10.1074/jbc.275.19.14198
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine 62 of the γ-Aminobutyric Acid Type A Receptor β2 Subunit Is an Important Determinant of High Affinity Agonist Binding

Abstract: The ␥-aminobutyric acid type A receptor (GABA A R) carries both high (K D ‫؍‬ 10 -30 nM) and low (K D ‫؍‬ 0.1-1.0 M) affinity binding sites for agonists. We have used site-directed mutagenesis to identify a specific residue in the rat ␤2 subunit that is involved in high affinity agonist binding. Tyrosine residues at positions 62 and 74 were mutated to either phenylalanine or serine and the effects on ligand binding and ion channel activation were investigated after the expression of mutant subunits with wild-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 48 publications
5
28
0
Order By: Relevance
“…Consistent with the location of these assembly signals to intersubunit contact points, the ␣/␥ signals (18,19,21) are located proximal to the GABA and benzodiazepine binding sites (22,23) formed at subunit interfaces between the ␣-␤ and ␣␥ subunits, respectively, and also the ␤2 high affinity GABA site (24). Similarly, the homologous region in 1 is an important component of the GABA binding domain (25).…”
mentioning
confidence: 57%
See 1 more Smart Citation
“…Consistent with the location of these assembly signals to intersubunit contact points, the ␣/␥ signals (18,19,21) are located proximal to the GABA and benzodiazepine binding sites (22,23) formed at subunit interfaces between the ␣-␤ and ␣␥ subunits, respectively, and also the ␤2 high affinity GABA site (24). Similarly, the homologous region in 1 is an important component of the GABA binding domain (25).…”
mentioning
confidence: 57%
“…In keeping with other studies (18,28), these authors found that Gln-67 and Trp-69 were essential for the production of functional receptors. Moreover, this region is not only important in the ␣1 subunit contribution to GABA binding, but the high affinity GABA binding site has been shown to be produced by the homologous region in ␤2 (␤2A interface to ␣1) (24). In addition, the benzodiazepine binding site on the ␥2 subunit resides within the same homologous region, with A79 (homologous position to Arg-66 in ␣1) lining the benzodiazepine binding pocket (23).…”
Section: Differential Gaba a Receptor Assemblymentioning
confidence: 99%
“…The residues homologous to ␣1F64 in the ␤2 (Tyr-62) and ␥2 (Phe-77) subunits do not seem to play a key role in agonist binding as mutation of ␤2Y62 and ␥2F77 resulted in a negligible shift in GABA sensitivity (12). However, a complete loss of high affinity binding was reported when ␤2Y62 was mutated to serine (13). They suggested that ␤2Y62 might be a component of the high affinity GABA binding site, but not part of the binding site linked to channel gating.…”
Section: Gabamentioning
confidence: 99%
“…The sequence of the bullfrog 1-like subunit revealed conservation of the rat 1 subunit Tyr-62 residue associated with high-affinity agonist binding (Newell et al 2000). Also, two GABA binding domains found on the rat 1 subunit (as well as subunits of other phyla) were conserved in the bullfrog 1-like subunit (rat Tyr-157-Thr-160 and Thr-202-Tyr-205; Amin & Weiss 1993).…”
Section: Discussionmentioning
confidence: 89%